2016
DOI: 10.5897/ajar2016-10870
|View full text |Cite
|
Sign up to set email alerts
|

Physiological quality of quinoa seeds submitted to different storage conditions

Abstract: Quinoa has grown importance in the world due to the nutritional quality of its grains and crop adaptability to diverse climatic conditions. One problem that limits its cultivation is the reduced viability of seeds during storage and the information is rather scarce. This work aimed at evaluating the physiological quality of quinoa seeds along time when submitted at storage conditions and packaging. An entirely randomized experiment was conducted on factorial scheme 2 x 3 x 6 with four repetitions. The treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Quinoa seed of initial seed quality of 80% germination and 8% moisture content can be stored hermetically for six months without loss of viability under ambient conditions (25-40°C and 50-60% RH) while after one-year storage germination declines to 15% [231]. Quinoa seed maintains physiological quality for longer periods (up to 300 days) in impermeable packaging and under low temperature (4 ± 2°C) [232]. It is also reported that quinoa seed with 5% moisture content at 5°C can be stored for 8 months with maximum viability [233], and this moisture content is also ideal for long term storage.…”
Section: Detection Of Saponins In Quinoamentioning
confidence: 99%
“…Quinoa seed of initial seed quality of 80% germination and 8% moisture content can be stored hermetically for six months without loss of viability under ambient conditions (25-40°C and 50-60% RH) while after one-year storage germination declines to 15% [231]. Quinoa seed maintains physiological quality for longer periods (up to 300 days) in impermeable packaging and under low temperature (4 ± 2°C) [232]. It is also reported that quinoa seed with 5% moisture content at 5°C can be stored for 8 months with maximum viability [233], and this moisture content is also ideal for long term storage.…”
Section: Detection Of Saponins In Quinoamentioning
confidence: 99%
“…Gelmond et al applied accelerated aging to obtain six different levels of vigor of sorghum seeds from an identical lot [6]. Souza et al also adopted an accelerated aging test during their study of the physiological quality of quinoa seeds under different storage conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Leaf length, breadth, thickness, petiole length, and area were computed using the averages of 30 measurements (10 plants per plot for each of the 3 different leaf and petiole sizes). The harvest was done manually, panicles were carefully removed to minimize grain spilling, then the panicles were threshed by a mechanical thresher, seeds were cleaned, and the seeds were held in an electric oven at 100 o C for 48 hours to regulate the moisture content to 12 percent, as advised by (Biru, 1978;de Jesus Souza et al, 2016). A digital caliper was used to measure the diameter of the stem and the thickness of the leaves (Digimatic Solar DC-S15 m, Mitutoyo, Japan).…”
Section: Data Collection and Measurementsmentioning
confidence: 99%